2021
DOI: 10.1038/s41467-020-20697-w
|View full text |Cite|
|
Sign up to set email alerts
|

Ionic shape-morphing microrobotic end-effectors for environmentally adaptive targeting, releasing, and sampling

Abstract: Shape-morphing uses a single actuation source for complex-task-oriented multiple patterns generation, showing a more promising way than reconfiguration, especially for microrobots, where multiple actuators are typically hardly available. Environmental stimuli can induce additional causes of shape transformation to compensate the insufficient space for actuators and sensors, which enriches the shape-morphing and thereby enhances the function and intelligence as well. Here, making use of the ionic sensitivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 42 publications
(17 reference statements)
0
106
0
Order By: Relevance
“…In 2021, Zheng et al (2021) designed ionic shape-morphing micro-robotic end-effectors (ISMEs) that can be used for environmental targeting, releasing and sampling, and have a gripping motion. The magnetic nanoparticles are encapsulated in an alginate monolayer, and the ISMEs are controlled by the external magnetic field to reach the target position.…”
Section: Stationary Electromagnet Control Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2021, Zheng et al (2021) designed ionic shape-morphing micro-robotic end-effectors (ISMEs) that can be used for environmental targeting, releasing and sampling, and have a gripping motion. The magnetic nanoparticles are encapsulated in an alginate monolayer, and the ISMEs are controlled by the external magnetic field to reach the target position.…”
Section: Stationary Electromagnet Control Systemsmentioning
confidence: 99%
“…The system consists of 8 electromagnetic coils with DT4 cores, which are distributed diagonally. The structure of this coil system is the same as that used by Diller et al (2013) and Li et al (2020), as shown in Figure 2D (Zheng et al, 2021). The specific modeling configuration of this electromagnetic coils is shown in Figure 1E (Pourkand and Abbott, 2018).…”
Section: Stationary Electromagnet Control Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the movement process of starfish preying on shellfish, Zheng et al [25] designed a sea star-like microrobot, the flexible tentacles of which can effectively conform to the outer contours of any target with autonomous deformation in a liquid environment for grasping and releasing. The robot has multiple actuation modes, for example, through trapping of magnetic microspheres or through encapsulating magnetic nanomaterials in the robot body, as shown in Figure 1.…”
Section: Magnetic Field Actuationmentioning
confidence: 99%
“…The micromachines applied to non-invasive medical interventions have attracted numerous attention since being proposed by Albert Hibbs and Richard Feynman in 1959. After decades of development, it has made great progress in a variety of microrobot fields, including actuation, control, navigation, and functionalization, laying the foundation for future clinical applications [ 1 , 3 , 5 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. However, how to accurately deliver microrobots to a specified position to perform medical tasks is still an unsolved problem due to the fact that manual control is inefficient and imprecise.…”
Section: Introductionmentioning
confidence: 99%